Azapolycyclic compounds and preparation methods and applications thereof
By developing aza polycyclic compounds with large conjugated structure and easy to form hydrogen bonds, it is used to prepare ultraviolet shielding materials, and the problems of single functions and potential toxic side effects of existing ultraviolet shielding agents are solved, and efficient and environmentally friendly ultraviolet absorption effect and long-term stability of the material are achieved.
Patent Information
- Application Number
- CN202310286296.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-03-22
AI Technical Summary
The existing ultraviolet shielding agents have a single function, and some substances may have toxic side effects and bioaccumulation in the human body and the environment, affecting ecological balance. At the same time, the compatibility of inorganic ultraviolet reflectors with materials is poor.
A aza polycyclic compound was developed with a large conjugated structure and easy to form hydrogen bonds for the preparation of ultraviolet shielding materials. The compound can be directly added to PE, PVC or PP resins, or prepared in conjunction with other UV absorbers to achieve efficient dispersion by microwave radiation.
It achieves efficient ultraviolet absorption performance, extends the service life of the material, and has good comprehensive performance, environmentally friendly and non-toxic, and has biological activity and broad-spectrum bactericidal properties.
Smart Images

Figure CN116535413B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of light shielding materials, and in particular to nitrogen heteropolycyclic compounds and preparation methods and applications thereof. Background Art
[0002] In recent decades, with the intensification of human activities, the problem of air pollution has become particularly serious, especially the large-scale use of artificial chemicals such as chlorofluorocarbons, which has damaged the ozone layer and caused stronger ultraviolet radiation to reach the earth. For polymer materials, long-term exposure to sunlight and absorption of ultraviolet energy will cause polymer degradation, reduce the mechanical properties and gloss of the polymer, and make it lose its use value.
[0003] UV absorber is a light stabilizer that can absorb sunlight and ultraviolet light from fluorescent light sources without any changes to itself. According to its own molecular structure characteristics, it converts the absorbed ultraviolet light into other forms that are harmless to the human body and releases it to prevent photo-oxidation reactions in the skin or polymer materials. UV absorbers are the earliest and most widely used anti-aging agents in industrial applications and are widely used in plastics, rubber, fibers, coatings, and papermaking. By absorbing ultraviolet rays to prevent the corrosion of materials by photo-aging, it plays an important role in extending the service life of materials and saving resources. With the high-tech development of synthetic technology and the continuous development of various new types of UV absorbers, products with higher technical added value are provided for light stabilization chemical technology. Under this framework, the research on ultraviolet shielding materials has received widespread attention from researchers. In particular, optically visible and transparent polymer composite materials with low-cost UV protection are the focus of current research. The selection of polymers with host matrices to prepare ultraviolet shielding films has excellent biocompatibility and harmless properties. Its unique mechanical and thermal properties also make it easy to form films. Therefore, the preparation of resin films with added ultraviolet absorbers as ultraviolet shielding materials has potential application value.
[0004] UV shielding agents are widely used. Various organic UV absorbers such as salicylates, benzophenones, benzotriazoles, substituted acrylonitriles, triazines and hindered amines have been developed; there are also various inorganic UV reflectors such as titanium dioxide, zinc oxide, talcum powder, clay, calcium carbonate, etc. However, the functions of existing UV shielding agents are relatively single, or such substances will produce toxic side effects after a certain amount of human intake, and they are easy to cause allergies and dermatitis when attached to the skin; studies have shown that some substances may also be an environmental hormone with potential bioaccumulation, interfering with the level of sex hormones in organisms, and continuously flowing into nature and accumulating to a certain extent, which will destroy the ecological balance (for example: Recently, researchers in many places have found that organic UV absorbers mainly based on benzophenone are difficult to decompose in the environment, and a large amount of residues have been found in soil and river water. Even after sewage treatment, they cannot be completely removed, and gradually become a new type of pollutant). Therefore, the content of such substances in various consumer products and the level of media migration that may enter the natural world have attracted widespread attention. Inorganic UV reflectors have poor compatibility with many materials such as resins, and many are not resistant to acids and alkalis, which restricts the processing and performance of the products.
[0005] Studies have shown that triazole derivatives have a variety of properties and have been used as medicine, pesticides, energetic materials and other fields, and their impact on the human body and the environment is relatively small. The triazolotriazine skeleton has the properties of a monocyclic triazole, and its electron-rich structure gives it unique properties. It has been initially developed and applied in liquid crystals and other fields. Although triazole and triazine compounds have been used as ultraviolet absorbers, their application scenarios still have certain limitations, but there is no clear report on the preparation and application of triazolotriazine as an ultraviolet absorber. Although there are some reports on the synthesis methods of triazolotriazine compounds, most of them are difficult to synthesize and have a very low yield, and are in the early stages of research and development. For example, in 2016, Alexandre et al. proposed a method for synthesizing tri-p-hydroxyphenyltriazolotriazine compounds, which needs to be reacted under argon protection. The synthesis conditions of this method are harsh and the yield is 60%. We have tried to synthesize tri-o-hydroxyphenyltriazolotriazine and tri-m-hydroxyphenyltriazolotriazine according to the conditions of this method, but we were unable to obtain the target compound. We optimized the scheme and changed the synthesis conditions to obtain the target compounds tri-o-hydroxyphenyltriazole and triazine and tri-m-hydroxyphenyltriazole compounds with yields of 78% and 75%, respectively. The yield of tri-p-hydroxyphenyltriazole and triazine compounds synthesized based on the optimized synthesis method reached 80%, and no inert gas protection was required, and the reaction time was significantly shortened. After performance characterization, we found that the ultraviolet absorption performance of tri-o-hydroxyphenyltriazole and triazine and tri-m-hydroxyphenyltriazole and triazine synthesized by us was better than that of tri-p-hydroxyphenyltriazole and triazine compounds. Therefore, our synthesized tri-o-hydroxyphenyltriazole and triazine and tri-m-hydroxyphenyltriazole and triazine are more suitable as ultraviolet absorbers and are used in the preparation of ultraviolet shielding materials. Summary of the invention
[0006] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0007] Another object of the present invention is to provide an aza-polycyclic compound having a large conjugated structure, being easy to form hydrogen bonds within and between molecules, and having excellent ultraviolet absorption performance. The aza-polycyclic compound can be directly added to PE, PVC or PP resin to prepare ultraviolet shielding materials, or can be prepared in conjunction with ultraviolet absorbers to prepare ultraviolet shielding materials. The aza-polycyclic compound ultraviolet absorber can be efficiently and uniformly dispersed into the resin by microwave radiation, thereby achieving efficient addition. Compared with traditional methods, the efficiency can be improved, and the surface of the aza-polycyclic ultraviolet shielding material can be more beautiful.
[0008] The invention also discloses a method for preparing an aza-polycyclic compound, wherein a substituted cyanophenol is used as a starting material, and reacts with an azide in a solvent to obtain a substituted hydroxyphenyltetrazolyl; the substituted hydroxyphenyltetrazolyl and cyanuric chloride are reacted in a solvent to obtain an aza-polycyclic compound, and the synthesis process is simple and easy, and the cost is low. The aza-polycyclic compound of the invention can be directly added to PE, PVC or PP resin to prepare an ultraviolet shielding material, or can be synergistically prepared with an ultraviolet absorber. The ultraviolet absorber of the aza-polycyclic compound can be quickly dispersed into the resin efficiently and uniformly by a microwave radiation method, thereby realizing efficient addition. Compared with the traditional method, the efficiency can be improved, and at the same time, the surface of the aza-polycyclic ultraviolet shielding material can be ensured to be more beautiful.
[0009] Another object of the present invention is to provide a method for preparing aza-polycyclic compounds, which uses substituted cyanophenol as a starting material, reacts with an azide in a solvent to obtain a substituted hydroxyphenyltetrazolyl; and reacts the substituted hydroxyphenyltetrazolyl and cyanuric chloride in a solvent to obtain the aza-polycyclic compound. The synthesis process is simple and easy, and the cost is low.
[0010] In order to achieve these purposes and other advantages according to the present invention, there is provided an azapolycyclic compound having the structure of the following formula (I):
[0011]
[0012] Among them, R1, R2, R3 and R4 are independently one of H, alkyl with less than 12 carbon atoms, salicylate, ketone with less than 12 carbon atoms, alcohol with less than 12 carbon atoms, carboxylic acid with less than 20 carbon atoms, azole ring, pyrimidine and oxazine ring.
[0013] Preferably, R1, R2, R3 and R4 are all H.
[0014] The purpose of the present invention can be further achieved by a method for preparing an azapolycyclic compound, comprising: using a substituted cyanophenol as a starting material, reacting it with an azide in a solvent to obtain a substituted hydroxyphenyltetrazolyl; reacting the substituted hydroxyphenyltetrazolyl and cyanuric chloride in a solvent, filtering out the precipitate, recovering the solvent in the filtrate to obtain a crude product, and purifying the crude product to obtain the target compound.
[0015] Preferably, the substituted cyanophenol has the following structure:
[0016]
[0017] Among them, R1, R2, R3 and R4 are independently one of H, alkyl with less than 12 carbon atoms, salicylate, ketone with less than 12 carbon atoms, alcohol with less than 12 carbon atoms, carboxylic acid with less than 20 carbon atoms, azole ring, pyrimidine and oxazine ring.
[0018] Preferably, the substituted hydroxyphenyltetrazolyl has the following structure:
[0019]
[0020] Among them, R1, R2, R3 and R4 are independently one of H, alkyl with less than 12 carbon atoms, salicylate, ketone with less than 12 carbon atoms, alcohol with less than 12 carbon atoms, carboxylic acid with less than 20 carbon atoms, azole ring, pyrimidine and oxazine ring.
[0021] Preferably, the reaction step of the substituted cyanophenol and the azide specifically comprises: dissolving the substituted cyanophenol in a solvent, adding NH4Cl and the azide, reacting at a temperature of 60 to 130°C for 0.5 to 24 hours, pouring the reaction solution into water for quenching, acidifying to pH = 1 with 6 mol / L HCl, and filtering to obtain the substituted hydroxyphenyl tetrazole after recrystallization in water.
[0022] Preferably, the azide is sodium azide, potassium azide or tetramethylsilane.
[0023] Preferably, the reaction temperature of the substituted hydroxyphenyltetrazolyl and cyanuric chloride is 90° C., the reaction time is 12 hours, and the solvent is methanol.
[0024] Preferably, the solvent is one or any combination of N,N-dimethylformamide, water, toluene, xylene, tetrahydrofuran, dimethyl sulfoxide, saturated nitrile with less than 14 carbon atoms, alcohol with less than 8 carbon atoms, ether with less than 8 carbon atoms and ketone with less than 8 carbon atoms.
[0025] The purpose of the present invention can be further achieved by using the nitrogen-polycyclic compound in the preparation of ultraviolet shielding materials, wherein the nitrogen-polycyclic compound can be directly added to PE, PVC or PP resin to prepare ultraviolet shielding materials, or can be synergistically prepared with salicylate, benzophenone, benzotriazole, substituted acrylonitrile, triazine or hindered amine ultraviolet absorbers to prepare ultraviolet shielding materials.
[0026] The present invention has at least the following beneficial effects:
[0027] 1. The molecular structure of the aza-polycyclic compound of the present invention contains a large amount of nitrogen and hydrogen elements, and hydrogen bonds are easily formed within and between molecules, and the compound has excellent ultraviolet absorption performance. The CH and NH on the azole ring have good reactivity, and the structure is easy to modify, and various functional groups can be introduced.
[0028] 2. The ultraviolet shielding material prepared from the nitrogen-polycyclic compound of the present invention has good light transmittance and strong absorption at 200nm-400nm, can be applied to polymers, has excellent anti-aging properties, and can extend the use time by several times.
[0029] 3. The ultraviolet shielding material prepared from the nitrogen-polycyclic compound of the present invention has good comprehensive performance, is environmentally friendly and non-toxic, does not produce toxic substances during the preparation process, is green and environmentally friendly, and in addition to excellent ultraviolet absorption performance, also has biological activity and exhibits broad-spectrum bactericidal properties.
[0030] 4. The nitrogen-polycyclic compound of the present invention can be quickly dispersed into the resin efficiently and uniformly by microwave radiation, thereby achieving efficient addition. Compared with the traditional method, this method can improve efficiency and ensure that the surface of the ultraviolet shielding material is more beautiful.
[0031] 5. The process technology for preparing the ultraviolet shielding material from the nitrogen-polycyclic compound of the present invention is mature, convenient and feasible, with small equipment investment and low product production cost, which can reduce the manufacturing cost of downstream products.
[0032] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The TTTL NMR of the nitrogen-containing polycyclic compound prepared in Example 1 of the present invention 1 H spectrum.
[0034] Figure 2 The TTTL NMR of the nitrogen-containing polycyclic compound prepared in Example 1 of the present invention 13 C spectrum.
[0035] Figure 3This is the infrared spectrum of the nitrogen-polycyclic compound TTTL prepared in Example 1 of the present invention.
[0036] Figure 4 This is the ultraviolet absorption spectrum of the nitrogen-polycyclic compound TTTL prepared in Example 1 of the present invention.
[0037] Figure 5 This is a high-resolution mass spectrum of the nitrogen-polycyclic compound TTTL prepared in Example 1 of the present invention.
[0038] Figure 6 This is a single crystal X-ray diffraction pattern of the nitrogen-polycyclic compound TTTL prepared in Example 1 of the present invention.
[0039] Figure 7 This is the ultraviolet absorption spectrum of the ultraviolet shielding material prepared in Example 1 of the present invention.
[0040] Figure 8 This is the ultraviolet transmittance spectrum of the ultraviolet shielding material prepared in Example 1 of the present invention.
[0041] Fig. 9 The NMR of the nitrogen-polycyclic compound TTTJ prepared in Example 8 of the present invention is 1 H spectrum.
[0042] Fig.10 The NMR of the nitrogen-polycyclic compound TTTJ prepared in Example 8 of the present invention is 13 C spectrum.
[0043] Fig.11 This is the infrared spectrum of the nitrogen polycyclic compound TTTJ prepared in Example 8 of the present invention.
[0044] Fig.12 This is the ultraviolet absorption spectrum of the nitrogen-polycyclic compound TTTJ prepared in Example 8 of the present invention.
[0045] Fig.13 This is the high-resolution mass spectrum of the nitrogen-polycyclic compound TTTJ prepared in Example 8 of the present invention.
[0046] Fig.14 This is the ultraviolet absorption spectrum of the ultraviolet shielding material prepared in Example 8 of the present invention.
[0047] Fig.15 This is the ultraviolet transmittance spectrum of the ultraviolet shielding material prepared in Example 8 of the present invention.
[0048] Fig.16 The NMR of the nitrogen-polycyclic compound TTTD prepared in Example 11 of the present invention is 1 H spectrum.
[0049] Fig.17 The NMR of the nitrogen-polycyclic compound TTTD prepared in Example 11 of the present invention is 13 C spectrum.
[0050] Fig.18 This is the infrared spectrum of the nitrogen polycyclic compound TTTD prepared in Example 11 of the present invention.
[0051] Fig.19 This is the ultraviolet absorption spectrum of the nitrogen-polycyclic compound TTTD prepared in Example 11 of the present invention.
[0052] Fig. 20 This is a high-resolution mass spectrum of the nitrogen-polycyclic compound TTTD prepared in Example 11 of the present invention.
[0053] Fig.21 This is the ultraviolet absorption spectrum of the ultraviolet shielding material prepared in Example 11 of the present invention.
[0054] Fig. 22 This is the ultraviolet transmittance spectrum of the ultraviolet shielding material prepared in Example 11 of the present invention.
[0055] Fig.23 The ultraviolet absorption spectra of TTTL, TTTJ, TTTD prepared in Examples 1, 8, and 11 of the present invention after being added to the resin with UV-0 and UV-327.
[0056] Fig.24 The ultraviolet absorption spectra of TTTL, TTTJ, TTTD prepared in Examples 1, 8 and 11 of the present invention after adding UV-0 and UV-327 to the resin and accelerating ultraviolet irradiation for 10 hours.
[0057] Fig.25 The ultraviolet absorption spectra of TTTL, TTTJ, TTTD prepared in Examples 1, 8 and 11 of the present invention after adding UV-0 and UV-327 to the resin and accelerating ultraviolet irradiation for 20 hours.
[0058] Fig.26 The ultraviolet absorption spectra of TTTL, TTTJ, TTTD prepared in Examples 1, 8 and 11 of the present invention after adding UV-0 and UV-327 to the resin and accelerating ultraviolet irradiation for 30 hours.
[0059] Fig. 27 The ultraviolet absorption spectra of TTTL, TTTJ, TTTD prepared in Examples 1, 8 and 11 of the present invention after adding UV-0 and UV-327 to the resin and accelerating ultraviolet irradiation for 40 hours.
[0060] Fig.28The ultraviolet absorption spectra of TTTL, TTTJ, TTTD prepared in Examples 1, 8 and 11 of the present invention after adding UV-0 and UV-327 to the resin and accelerating ultraviolet irradiation for 50 hours.
[0061] Fig.29 The ultraviolet transmittance of different mass fractions of TTTJ prepared in Example 8 of the present invention after being added to the resin.
[0062] Fig.30 The ultraviolet transmittance of different mass fractions of TTTJ prepared in Example 1 of the present invention after being added to the resin.
[0063] Fig.31 The carbonyl index of TTTL, TTTJ and TTTD prepared in Examples 1, 8 and 11 of the present invention after being added to the resin changes with the accelerated ultraviolet irradiation time.
[0064] Fig.32 These are morphology pictures of the ultraviolet shielding materials prepared from TTTL, TTTJ and TTTD prepared in Examples 1, 8 and 11 of the present invention. DETAILED DESCRIPTION
[0065] The present invention will be further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0066] It should be understood that terms such as “having”, “including” and “comprising” used herein do not specify the existence or addition of one or more other elements or combinations thereof.
[0067] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.
[0068] The synthesis of tetrazole in the following examples was prepared by reference to the synthesis method in “Dal-BóA G, Cisneros GGL, Cercena R, et al. Synthesis, electrochemical, thermal and photophysical characterization of photoactive discotic dyes based on the tris-[1,2,4]-triazolo-[1,3,5]-triazine core[J]. Dyes and Pigments, 2016, 135: 49-56.” and optimized.
[0069] <Example 1>
[0070] Aza-polycyclic compounds, the structural formula of which is as follows:
[0071]
[0072] The specific synthesis steps are as follows:
[0073] (1) 0.715 g of 2-cyanophenol, 0.963 g of NH4Cl, 25 ml of DMF, and 1.17 g of sodium azide were added to a three-necked flask in sequence, and the mixture was heated to 130°C for reaction for 10 hours. The solution was poured into 100 ml of water for quenching, acidified to pH = 1 with 6 mol / L HCl, recrystallized in water, and filtered to obtain 5-(-2-hydroxyphenyl)tetrazolyl;
[0074] (2) Add 1 g of 5-(2-hydroxyphenyl)tetrazolyl and 16 ml of 3 mol / L NaOH aqueous solution into a three-necked flask. After complete dissolution, place the solution at 0°C for reaction, slowly add 0.674 g of glacial acetic anhydride dropwise, stir for 10 min, filter, and perform column chromatography to obtain 5-(2-acetoxyphenyl)tetrazolyl as a white solid;
[0075] (3) 1.84 g 5-(2-acetoxyphenyl)tetrazolyl, 4.98 g anhydrous K2CO3, 0.55 g cyanuric chloride, and 80 ml methanol were added to a three-necked flask in sequence, and the mixture was heated to 90°C for reaction for 12 hours, filtered, and the filtrate was collected and subjected to rotary evaporation. The powder obtained by rotary evaporation was dissolved in methanol, and sodium hydroxide was added to adjust the pH value of the reaction system to 8-10. The mixture was reacted at room temperature for 4 hours. After the reaction, the pH value was adjusted to weak acidity with dilute hydrochloric acid. A white solid precipitated, which was filtered and purified by column chromatography to obtain tri-(2-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine (TTTL). The yield was 78.3%. The NMR of the prepared compound TTTL 1 H spectrum see Figure 1 ,magnetic 13 C spectrum see Figure 2 、Infrared spectrum Figure 3 , UV absorption spectrum Figure 4 , high resolution mass spectrometry Figure 5 , single crystal X-ray diffraction pattern Figure 6 .
[0076] The steps of using the nitrogen-polycyclic compound synthesized in Example 1 to prepare the ultraviolet shielding material are as follows:
[0077] PVC resin and tri-(2-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine were dissolved in 30 mL DMF, wherein the total mass of PVC and tri-(2-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine was 1 g, and the mass fractions of tri-(2-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine were 0.5, 1, and 1.5 wt %, respectively. After being evenly mixed, the mixture was sealed and placed in a microwave generator for microwave radiation reaction, with a reaction time of 10 min and a reaction temperature of 40°C. The reactant was then cast on a smooth and clean glass plate, placed in a vacuum drying oven at 80°C and dried for 8 hours, then immersed in deionized water to remove excess solvent, and finally vacuum dried at 40°C for 10 hours to obtain a UV shielding material product. The UV absorption spectrum of the prepared UV shielding material is shown in Figure 7 , UV transmission spectrum Figure 8 .
[0078] <Example 2>
[0079] The reaction solvent used in the TTTL synthesized in this example is dimethyl sulfoxide, and the remaining experimental operations are the same as those in Example 1, to prepare a nitrogen-containing heteropolycyclic compound with a yield of 72.6%.
[0080] <Example 3>
[0081] The reaction solvent used in the synthesis of TTTL in this example is tetrahydrofuran, and the remaining experimental operations are the same as those in Example 1, to prepare a nitrogen-containing heteropolycyclic compound with a yield of 71.1%.
[0082] <Example 4>
[0083] The reaction solvent used in the synthesis of TTTL in this example is N,N-dimethylformamide, and the remaining experimental operations are the same as those in Example 1, to prepare a nitrogen-containing heteropolycyclic compound with a yield of 68.9%.
[0084] <Example 5>
[0085] The reaction temperature in step (3) of the TTTL synthesized in this example is 80° C., and the remaining experimental operations are the same as those in Example 1, to prepare a nitrogen-containing heteropolycyclic ultraviolet absorber with a yield of 66.3%.
[0086] <Example 6>
[0087] The experimental operation of synthesizing tri-(2-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine in this embodiment is the same as that in embodiment 1, after which PP resin and tri-(2-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine are dissolved in 30 mL DMF, with a total mass of 1 g, and the mass fractions of tri-(2-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine are 0.5, 1, and 1.5 wt %, respectively. After being mixed evenly, the mixture is sealed and placed in a microwave generator for microwave radiation reaction, with a reaction time of 10 min and a reaction temperature of 40° C. The reactant is then cast on a smooth and clean glass plate, placed in a vacuum drying oven at 80° C. and dried for 8 hours, then immersed in deionized water to remove excess solvent, and finally vacuum dried at 40° C. for 10 hours to obtain a UV shielding material product.
[0088] <Example 7>
[0089] The experimental operation of synthesizing tri-(2-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine in this embodiment is the same as that in embodiment 1, after which PE resin and tri-(2-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine are dissolved in 30mL DMF, with a total mass of 1g, and the mass fractions of tri-(2-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine are 0.5, 1, and 1.5wt%, respectively. After uniform mixing, the mixture is sealed and placed in a microwave generator for microwave radiation reaction, with a reaction time of 10min and a reaction temperature of 40°C. The reactant is then cast on a smooth and clean glass plate, placed in a vacuum drying oven at 80°C and dried for 8 hours, then immersed in deionized water to remove excess solvent, and finally vacuum dried at 40°C for 10 hours to obtain a UV shielding material product.
[0090] <Example 8>
[0091] Aza-polycyclic compounds, the structural formula of which is as follows:
[0092]
[0093] The specific synthesis steps are as follows:
[0094] (1) 0.715 g 3-cyanophenol, 0.963 g NH4Cl, 25 ml DMF, and 1.17 g sodium azide were added to a three-necked flask in sequence, and heated to 130°C for reaction for 10 hours. The solution was poured into 100 ml water for quenching, acidified to pH = 1 with 6 mol / L HCl, recrystallized in water, and filtered to obtain 5-(-3-hydroxyphenyl)tetrazole;
[0095] (2) Add 1 g of 5-(3-hydroxyphenyl)tetrazolyl and 16 ml of 3 mol / L NaOH aqueous solution into a three-necked flask. After complete dissolution, place the solution at 0°C for reaction, slowly add 0.674 g of glacial acetic anhydride dropwise, stir for 10 min, filter, and perform column chromatography to obtain 5-(2-acetoxyphenyl)tetrazolyl as a white solid;
[0096] (3) 1.84 g 5-(3-acetoxyphenyl)tetrazolyl, 4.98 g anhydrous K2CO3, 0.55 g cyanuric chloride, and 80 ml methanol were added to a three-necked flask in sequence, and the mixture was heated to 90°C for reaction for 12 hours, filtered, and the filtrate was collected and subjected to rotary evaporation. The powder obtained by rotary evaporation was dissolved in methanol, and sodium hydroxide was added to adjust the pH value of the reaction system to 8-10. The mixture was reacted at room temperature for 4 hours. After the reaction, the pH value was adjusted to weak acidity with dilute hydrochloric acid. A white solid was precipitated, filtered, and purified by column chromatography to obtain tri-(2-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine (TTTJ) with a yield of 75.4%. The NMR of the prepared compound TTTJ showed that 1 H spectrum see Fig. 9 ,magnetic 13 C spectrum see Fig.10 、Infrared spectrum Fig.11 , UV absorption spectrum Fig.12 , high resolution mass spectrometry Fig.13 .
[0097] The steps of using the nitrogen-polycyclic compound synthesized in Example 8 to prepare the ultraviolet shielding material are as follows:
[0098] PVC resin and tris-(3-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine were dissolved in 30 mL DMF, wherein the total mass of PVC and tris-(3-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine was 1 g, and the mass fractions of tris-(3-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine were 0.5, 1, and 1.5 wt %, respectively. After being evenly mixed, the mixture was sealed and placed in a microwave generator for microwave radiation reaction, with a reaction time of 10 min and a reaction temperature of 40°C. The reactant was then cast on a smooth and clean glass plate, placed in a vacuum drying oven at 80°C and dried for 8 hours, then immersed in deionized water to remove excess solvent, and finally vacuum dried at 40°C for 10 hours to obtain a UV shielding material product. The UV absorption spectrum of the prepared UV shielding material is shown in Fig.14 , UV transmission spectrum Fig.15 .
[0099] <Example 9>
[0100] The experimental operation of synthesizing tri-(3-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine in this embodiment is the same as that in embodiment 8, after which PE resin and tri-(3-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine are dissolved in 30mL DMF, with a total mass of 1g, and the mass fractions of tri-(3-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine are 0.5, 1, and 1.5wt%, respectively. After uniform mixing, the mixture is sealed and placed in a microwave generator for microwave radiation reaction, with a reaction time of 10min and a reaction temperature of 40°C. The reactant is then cast on a smooth and clean glass plate, placed in a vacuum drying oven at 80°C and dried for 8 hours, then immersed in deionized water to remove excess solvent, and finally vacuum dried at 40°C for 10 hours to obtain a UV shielding material product.
[0101] <Example 10>
[0102] The experimental operation of synthesizing tri-(3-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine in this embodiment is the same as that in embodiment 8, after which PE resin and tri-(3-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine are dissolved in 30mL DMF, with a total mass of 1g, and the mass fractions of tri-(3-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine are 0.5, 1, and 1.5wt%, respectively. After uniform mixing, the mixture is sealed and placed in a microwave generator for microwave radiation reaction, with a reaction time of 10min and a reaction temperature of 40°C. The reactant is then cast on a smooth and clean glass plate, placed in a vacuum drying oven at 80°C and dried for 8 hours, then immersed in deionized water to remove excess solvent, and finally vacuum dried at 40°C for 10 hours to obtain a UV shielding material product.
[0103] <Example 11>
[0104] Aza-polycyclic compounds, the structural formula of which is as follows:
[0105]
[0106] The specific synthesis steps are as follows:
[0107] (1) 0.715 g of 2-cyanophenol, 0.963 g of NH4Cl, 25 ml of DMF, and 1.17 g of sodium azide were added to a three-necked flask in sequence, and the mixture was heated to 130°C for reaction for 10 hours. The solution was poured into 100 ml of water for quenching, acidified to pH = 1 with 6 mol / L HCl, recrystallized in water, and filtered to obtain 5-(-4-hydroxyphenyl)tetrazole;
[0108] (2) Add 1 g of 5-(4-hydroxyphenyl)tetrazolyl and 16 ml of 3 mol / L NaOH aqueous solution into a three-necked flask. After complete dissolution, place the solution at 0°C for reaction, slowly add 0.674 g of glacial acetic anhydride dropwise, stir for 10 min, filter, and perform column chromatography to obtain 5-(2-acetoxyphenyl)tetrazolyl as a white solid;
[0109] (3) Add 1.84 g 5-(4-acetoxyphenyl)tetrazolyl, 4.98 g anhydrous K2CO3, 0.55 g cyanuric chloride and 80 ml methanol to a three-necked flask, heat to 90°C for reaction for 12 hours, filter, collect the filtrate and evaporate, dissolve the evaporated powder in methanol, add sodium hydroxide to adjust the pH value of the reaction system to 8-10, react at room temperature for 4 hours, adjust the pH to weak acidity with dilute hydrochloric acid after the reaction, and a white solid precipitates, filter, and purify by column chromatography to obtain tri-(4-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine (TTTD). The yield is 60.2%. The NMR of the prepared compound TTTD 1 H spectrum see Fig.16 ,magnetic 13 C spectrum see Fig.17 、Infrared spectrum Fig.18 , UV absorption spectrum Fig.19 , high resolution mass spectrometry Fig. 20 .
[0110] The steps of using the nitrogen-polycyclic compound synthesized in Example 11 to prepare the ultraviolet shielding material are as follows:
[0111] PVC resin and tri-(4-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine were dissolved in 30 mL DMF, wherein the total mass of PVC and tri-(4-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine was 1 g, and the mass fractions of tri-(4-hydroxyphenyl)-[1,2,4]-triazolo-[1,3,5]-triazine were 0.5, 1, and 1.5 wt %, respectively. After being evenly mixed, the mixture was sealed and placed in a microwave generator for microwave radiation reaction, with a reaction time of 10 min and a reaction temperature of 40°C. The reactant was then cast on a smooth and clean glass plate, placed in a vacuum drying oven at 80°C and dried for 8 hours, then immersed in deionized water to remove excess solvent, and finally vacuum dried at 40°C for 10 hours to obtain a UV shielding material product. The UV absorption spectrum of the prepared UV shielding material is shown in Fig.21 , UV transmission spectrum Fig. 22 .
[0112] <Example 12>
[0113] 1. Simulate ultraviolet radiation
[0114] like Figures 23 to 28 , the PVC / TTTL, PVC / TTTJ and PVC / TTTD films synthesized in Example 1, Example 8 and Example 11 were placed in a UV aging box to simulate outdoor UV irradiation. According to the power of the UV aging chamber and the distance between the sample and the light source, the UV irradiation was accelerated in the aging chamber for 1 hour, which was equivalent to 100 hours of outdoor irradiation under normal circumstances. The pure PVC film was burnt yellow after 50 hours, turned dark brown after 100 hours, and broke over a large area after 150 hours, and the color darkened. The aging degree of the PVC / TTTD film was better than that of the pure PVC film, but the effect was not significant. The anti-aging effect of the PVC / TTTJ film is comparable to that of UV-0 and UV-327 sold on the market. The PVC / TTTL film has excellent UV absorption effect and stronger anti-aging ability than UV-0 and UV-327 sold on the market. After 150 hours of irradiation, only partial yellowing occurred, and the integrity of the film remained well. The aging speed of pure PVC film is the fastest. Adding UV absorbers TTTL and TTTJ to the PVC film can significantly reduce the aging speed, maintain the integrity of the film, and reduce color changes. These results show that the nitrogen-polycyclic compound TTTL synthesized in Example 1 and the nitrogen-polycyclic compound TTTJ synthesized in Example 8 can be used as UV absorbers with good performance.
[0115] 2. Effect of UV absorber mass fraction on the anti-aging ability of PVC film
[0116] In order to study the effect of the mass fraction of UV absorber on the anti-aging ability of PVC film, samples with 0.5wt%, 1.0wt% and 1.5wt% were prepared. The UV-visible transmission spectra of the films were measured in the wavelength range of 200-600nm. The results are as follows: Fig.29 and 30As shown. It is worth noting that pure PVC exhibits high transmittance in the 220-800nm region, while the UV transmittance of PVC / TTTL and PVC / TTTJ films below 400nm is negligible, and the transparency above 400nm exceeds 85%, indicating good transparency in the visible light range. After TTTL and TTTJ are incorporated into PVC, the UV transmittance of PVC / TTTL and PVC / TTTJ films is significantly reduced, and the UV absorption range of the films increases with the increase of TTTL and TTTJ mass fractions. With the increase of TTTL and TTTJ mass fractions, the transmittance of PVC / TTTL and PVC / TTTJ films above 400nm gradually decreases, and the transmittance of 1.5wt% PVC / TTTL and PVC / TTTJ films drops to below 80%, thus affecting the transparency of PVC films. These results show that PVC films with appropriate TTTL and TTTJ mass fractions can effectively absorb UV rays and maintain sufficient transparency in the visible light range, while having anti-aging properties. Although 1.5wt% PVC / TTTL and PVC / TTTJ films have stronger UV absorption than 1.0wt% PVC / TTTL and PVC / TTTJ films, film transparency is also critical. Therefore, 1.0wt% TTTL and TTTJ content is the most appropriate.
[0117] 3. Carbonyl index (CI) was used to evaluate the degradation degree of PVC film
[0118] The carbonyl index (CI) was used to evaluate the degradation degree of PVC film. The carbonyl index (CI) decline curves of PVC and PVC / TTTL, PVC / TTTJ and PVC / TTTD films are shown in Figure 2. Fig.31 As shown. CI is an indicator to measure the absorbance of carbonyl group relative to the reference band, and the change of CI value reflects the degree of degradation of the film. As can be seen from the broken line in the figure, the CI values of PVC / TTTD, PVC / TTTJ and PVC / TTTL films have all decreased. After 10 hours of irradiation, the CI values of PVC, PVC / TTTD, PVC / TTTJ and PVC / TTTL films decreased by 22.0%, 14.1%, 15.3% and 13.0%, respectively. After 20 hours of ultraviolet irradiation, the CI value of the film slowly decreased. In addition, compared with pure PVC film, the CI value of PVC / TTTD, PVC / TTTJ and PVC / TTTL films decreased by less than 5% after 40 hours of ultraviolet irradiation. These results show that TTTL, TTTJ and TTTD have high anti-aging ability.
[0119] Fig.32The UV shielding materials prepared in Examples 1, 8, and 11 (from left to right are the appearance pictures of the UV shielding materials prepared by the nitrogen-polycyclic compounds of Examples 1, 8, and 11). The UV shielding materials prepared by TTTL and TTTJ have good light transmittance, strong absorption at 200nm-400nm, can shield ultraviolet radiation, have excellent anti-aging properties, and can extend the use time of polymers by several times. This UV shielding material product has good comprehensive performance, is environmentally friendly and non-toxic, and has biological activity in addition to excellent UV absorption performance, showing broad-spectrum bactericidal properties. However, the UV shielding material product prepared by TTTD has poor performance in the above aspects.
[0120] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and the embodiments. It can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily realized. Therefore, without departing from the general concept defined by the claims and equivalent scope, the present invention is not limited to the specific details and the illustrations shown and described here.
Claims
1. A nitrogen polycyclic compound having the following structure: or .
2. A method for preparing the azapolycyclic compound according to claim 1, comprising: 2-Cyanophenol and 3-cyanophenol are used as starting materials, reacted with azide in a solvent to obtain substituted hydroxyphenyltetrazolyl; the substituted hydroxyphenyltetrazolyl and cyanuric chloride are reacted in a solvent, the precipitate is filtered off, the solvent in the filtrate is recovered to obtain a crude product, and the crude product is purified to obtain the target compound.
3. The method of claim 2, wherein: The reaction steps of 2-cyanophenol, 3-cyanophenol and azide specifically include: dissolving 2-cyanophenol and 3-cyanophenol in a solvent, adding NH4Cl and azide, reacting at a temperature of 60 to 130°C for 0.5 to 24 hours, pouring the reaction solution into water for quenching, acidifying to pH=1 with 6 mol / L HCl, and filtering to obtain substituted hydroxyphenyltetrazolyl after recrystallization in water.
4. The method of claim 3, wherein: The azide is sodium azide, potassium azide or tetramethylsilane.
5. The method of claim 2, wherein: The reaction temperature of the substituted hydroxyphenyltetrazolyl and cyanuric chloride is 90° C., the reaction time is 12 hours, and the solvent is methanol.
6. The method of claim 3, wherein: The solvent is one or any combination of N,N-dimethylformamide, water, toluene, xylene, dimethyl sulfoxide, saturated nitrile with less than 14 carbon atoms, alcohol with less than 8 carbon atoms, ether with less than 8 carbon atoms and ketone with less than 8 carbon atoms.
7. Use of the nitrogen heteropolycyclic compound according to claim 1 in preparing ultraviolet shielding materials, wherein: The nitrogen-polycyclic compound can be directly added to PE, PVC or PP resin to prepare ultraviolet shielding materials, or can be used in conjunction with salicylate, benzophenone, benzotriazole, substituted acrylonitrile, triazine or hindered amine ultraviolet absorbers to prepare ultraviolet shielding materials.
Citation Information
Patent Citations
Thermal activation delayed fluorescence material and application thereof
CN111393448A